How to Influence Others? Synthetic Personalization and Social Semiotic Analysis of Genders - Firdausi, Annisa Nurul; Andriyanti, Erna; Ashadi, Ashadi (Humanus, 2023)
Within the last 20 years, TED has become an influential platform that provides knowledge and education by directing speakers on giving motivational speeches. This paper aims to analyze gender attitudes while delivering the speech and how they influence the audience. This study applied a descriptive qualitative method by using Synthetic Personalization by Fairclough (2001) and a Social-semiotic approach by Van Leeuwen (2008) to the selected TED videos to analyze the data and corpus linguistics, namely AntConc, as the tool to analyze the vocabularies, first-person and second-person concordances presented. The findings show 1.101 vocabularies used by men and 1.156 vocabularies that denote synthetic personalization used by women. Although the strategies they used are different, men’s and women’s speeches have successfully influenced the audience by immersing synthetic personalization to bring intimate, engagement, and personal relationships towards the mass audience by bringing up the feeling of ‘similarity’. The social-semiotic covers social distance and social interaction between men and women toward the audiences. Women are more socially considerate while men are more direct in their speech. The distance and interactions are subjected as a form of representation of closeness.